2016
DOI: 10.1111/bcpt.12639
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Effects of the Neolignan 2,3‐Dihydrobenzofuran Against Leishmania Amazonensis

Abstract: Leishmaniasis is an infectious disease complex caused by protozoa from the Leishmania genus, which presents a broad spectrum of clinical manifestations: cutaneous, mucocutaneous and visceral forms. The current treatments are unsatisfactory considering that few drugs are available and present some level of toxicity. Many lignans and neolignans have been used for the development of new antileishmania drugs. The capability in vitro of the neolignan 2,3-dihydrobenzofuran (2,3-DBF), a commonly found constituent of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(16 citation statements)
references
References 48 publications
0
15
0
1
Order By: Relevance
“…Plants constitute an important source of new pharmaceuticals, and studies have been developed in an attempt to identify the bioactive molecules that could be employed for this purpose, such as quinoline, alkaloids, coumarins, tannins, saponins, cyclosporine, among others . As a consequence, an increasing awareness of the potential of these compounds might lead to the development of novel drugs for the treatment of neglected diseases, as the impact of natural products on drug discovery is considerable, not only for cancer, but also for parasitic infections .…”
mentioning
confidence: 99%
“…Plants constitute an important source of new pharmaceuticals, and studies have been developed in an attempt to identify the bioactive molecules that could be employed for this purpose, such as quinoline, alkaloids, coumarins, tannins, saponins, cyclosporine, among others . As a consequence, an increasing awareness of the potential of these compounds might lead to the development of novel drugs for the treatment of neglected diseases, as the impact of natural products on drug discovery is considerable, not only for cancer, but also for parasitic infections .…”
mentioning
confidence: 99%
“…Interestingly, a low cytotoxic potential was observed for LIC‐A on mammalian cell line (Vero), which is in accordance to recently observations on Vero cells and other cell lines (Meleti et al, 2020; Morais et al, 2020). The interest in neolignans have increased since they exhibit low toxicity potential (de Castro Oliveira et al, 2017; Dias et al, 2017; Zálešák, Bon, & Pospíšil, 2019). Considering a higher selectivity index for the parasite compared with the mammalian cells, the results obtained in the present study reinforce the potential relevance of LIC‐A against S. mansoni .…”
Section: Discussionmentioning
confidence: 99%
“…Hydroquinone occurs naturally in various medicinal plants [61,62], it has been reported to be allelochemic, antimicrobial, antihepatomic, antilithic, antimelanomic, antimelasmic, uroantiseptic , antimitotic, and antipertussive [63][64][65]. Benzofuran, 2,3-dihydro is a coumaran and research has shown that it possesses antiinflammatory, antidiarrheal, antileishmanial, immunomodulatory, antimicrobial and antihelminthic activities [66][67][68]. Octadecanoic acid is a flavouring agent which is hypocholesterolemic [69].…”
Section: Discussionmentioning
confidence: 99%